Benchmarking the Lisbon Strategy - Demosthenes Ioannou; Marien Ferdinandusse; Marco Lo Duca; Wouter Coussens (European Central Bank (ECB), 2008)
This paper reviews the governance framework of the Lisbon Strategy and discusses the specific option of increasing the role of benchmarking as a means of improving the implementation record of structural reforms in the European Union. Against this background, the paper puts forward a possible avenue for developing a strong form of quantitative benchmarking, namely ranking. The ranking methodology relies on the construction of a synthetic indicator using the “benefit of the doubt” approach, which acknowledges differences in emphasis among Member States with regard to structural reform priorities. The methodology is applied by using the structural indicators that have been commonly agreed by the governments of the Member States, but could also be used for ranking exercises on the basis of other indicators.
Keywords: D02; P11; P16; C43; C61; 330; Lisbon Strategy; economic governance; benchmarking; benefit of the doubt weighting.; EU-Wirtschaftspolitik; Benchmarking; Governance-Ansatz; Ranking-Verfahren; EU-Staaten